2020
DOI: 10.1371/journal.pone.0234830
|View full text |Cite
|
Sign up to set email alerts
|

Climate gradients, and patterns of biodiversity and biotic homogenization in urban residential yards

Abstract: Residential yards constitute a substantive biodiverse greenspace within urban areas. This biodiversity results from a combination of native and non-native species and can contribute to biotic homogenization. Geographical climatic patterns affect the distribution of native species and may differently affect non-native species. In this study, we examined biodiversity and biotic homogenization patterns of yard-dwelling land snails across 12 towns in Oklahoma and Kansas (USA). The 3 x 4 array of towns incorporated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…There is very little information on non-captive land snails associated with zoos in the United States; indeed, the only reference we found was a statement that Ventridens demissus was a common snail in the Atlanta Zoo, where it was also the only species found on the Zoo's green roofs [26]. This species was found at all sites in our survey and is common in both regional plant nurseries [22] and yards [25,35]. An interesting observation associated with this species is the rasping of empty shells, presumably as a source of calcium.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There is very little information on non-captive land snails associated with zoos in the United States; indeed, the only reference we found was a statement that Ventridens demissus was a common snail in the Atlanta Zoo, where it was also the only species found on the Zoo's green roofs [26]. This species was found at all sites in our survey and is common in both regional plant nurseries [22] and yards [25,35]. An interesting observation associated with this species is the rasping of empty shells, presumably as a source of calcium.…”
Section: Discussionmentioning
confidence: 80%
“…Nearly all OKC Zoo sites had both native and non-native species, with only a single site having two non-native species and no native species. This mix of native and non-native species is typical of regional urban yards [25,30,35], whereas parks and natural areas with fewer plantings may have relatively fewer non-native species of snails [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the presence of mucus from snails of different species had no statistical effect on resting site selection, except for the apparent avoidance of mucus from individuals of Patera appressa . During previous fieldwork by E. A. Bergey (e.g., Bergey, 2019; Bergey & Whipkey, 2020), resting individuals of C. aspersum were not observed in association with any other snail taxa, either where resting on vertical surfaces (e.g., on house foundations) or in sheltering locations (e.g., under logs). In contrast to our results, avoidance, as indicated by a lack of trail following, was found among five species of Hawaiian tree snails that did not follow trails of other species but followed trails of conspecifics (Holland et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Other studies are showing comparable results for terrestrial habitats. Thus, precipitation seasonality was singled as the best predictor of soil invertebrate richness in agricultural ecosystems in China 49 , while, in urban habitats, snail abundance was negatively associated with increasing rainfall and positively but weakly associated with higher temperatures during the winter 50 . The effect of precipitation seasonality on species richness, in our case, could be just another way to capture the effect of Submediterranean climate, characterized by a lower seasonality of precipitation.…”
Section: Discussionmentioning
confidence: 93%